Hubungan Pengetahuan Dan Pola Asuh Ibu Dengan Kemandirian Toilet Training Pada Anak Pra sekolah - Anisa Sekar Kiranti; Tuti Asrianti Utami; Wilhelmus Hary Susilo (STIKES Ngesti Waluyo, 2025)
Toilet training is a process in the development of preschool children aged 3-6 years in the process of urination and defecation. The purpose of this study was to determine the relationship between knowledge and parenting patterns of mothers and the independence of toilet training in preschool children at RA Darul Hikmah. The research method was descriptive correlational with a cross-sectional approach. The sampling technique involved a total of 80 respondents, including mothers who have preschool-aged children. The results of the study explained that of the 80 respondents, most were aged 19-35 years as many as 72 respondents (90.0%), housewife occupation as many as 61 respondents (76.3%), education level (high school) as many as 43 respondents (53.8%), parity with having 2 children as many as 47 respondents (58.8%), good knowledge level as many as 41 respondents (51.2%), democratic parenting patterns as many as 38 respondents (47.5%), and toilet training independence as many as 41 respondents (51.2%). Kendal's Tau-b analysis revealed no correlation between knowledge (p-value = 0.447) and parenting styles (p-value = 0.643) and toilet training independence. Mothers should train their children to toilet train from an early age, not only providing instructions but also directing them appropriately.